2012
DOI: 10.1530/rep-11-0391
|View full text |Cite
|
Sign up to set email alerts
|

FSH withdrawal improves developmental competence of oocytes in the bovine model

Abstract: Combinations of genetic, environmental, and management factors are suspected to explain the loss in fertility observed for over 20 years in dairy cows. In some cases, IVF is used. When compared with in vivo embryo production, IVF resulted in low success rates until the FSH coasting process (FSH starvation after superstimulation) was introduced in 2002. Increased competence associated with FSH withdrawal of aspirated oocyte for in vitro maturation and IVF has not been optimized nor explained yet. The goal here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 26 publications
5
78
0
10
Order By: Relevance
“…This period of FSH withdrawal is part of the regimen for a precise reason. In fact, experiments in the cow showed that a short period of hormone deprivation after FSH priming improves oocyte quality by inducing mild atretic effects (Nivet et al, 2012). Atresia is usually considered a manifestation of follicle demise.…”
Section: Follicle Stimulating Hormone Primingmentioning
confidence: 99%
“…This period of FSH withdrawal is part of the regimen for a precise reason. In fact, experiments in the cow showed that a short period of hormone deprivation after FSH priming improves oocyte quality by inducing mild atretic effects (Nivet et al, 2012). Atresia is usually considered a manifestation of follicle demise.…”
Section: Follicle Stimulating Hormone Primingmentioning
confidence: 99%
“…Dentre essas biotécnicas, a produção in vitro de embriões (PIVE) merece destaque, pois possibilita a obtenção de um grande número de embriões viáveis para a produção animal e investigação científica (Nivet et al, 2012;Carrocera, Caamaño, Trigal, Martín, & Díez, 2016).…”
Section: Introductionunclassified
“…El desarrollo potencial de un embrión depende del ovocito del cual se originó; por lo tanto el proceso de maduración por medio del cual el ovocito adquiere competencia, es crítico para generar embriones eficientes que originen individuos sanos después de ser implantados (4) . En los animales domésticos como el bovino, uno de los principales problemas a los que se enfrenta la fertilización in vitro es el bajo porcentaje de blastocistos viables obtenidos a partir de ovocitos madurados in vitro (5,6) . De acuerdo a la experiencia de diversos grupos de investigación (7)(8)(9), en los sistemas bovinos, del total de ovocitos que se someten a maduración in vitro (IVM) sólo se logra obtener aproximadamente un 40 % de blastocistos viables; lo que es muy diferente a lo observado a partir de ovocitos madurados in vivo, donde el porcentaje de blastocistos viables obtenidos es cercano al 80 % .…”
Section: Introductionunclassified
“…The potential development of an embryo depends on the oocyte, from which it originated; therefore the mature process by means the oocyte acquires competition, is critical to generate efficient embryos that originate healthy individuals after being implanted (4) . In domestic animals like cattle, one of the main problems faced by in vitro fertilization is the low percentage of viable blastocysts derived from in vitro matured oocytes (5,6) . According to the experience of different research groups (7)(8)(9) in cattle systems, the total number of oocytes undergoing in vitro maturation (IVM) only manages to get about 40 % of the viable blastocysts; versus in vivo matured oocytes, where the percentage of viable blastocysts obtained is close to 80 %.…”
Section: Introductionmentioning
confidence: 99%